Success rate of two different methods of ilioinguinal-iliohypogastric nerve block in children inguinal surgery - Mahin Seyedhejazi; Omid Ranjbar Daemi; Reza Taheri; Morteza Ghojazadeh (Wolters Kluwer Medknow Publications, 2013)
Background: The ilioinguinal-iliohypogastric (ILIH) nerve block is a safe, effective, and easy to perform in order to provide analgesia for a variety of inguinal surgical procedures in pediatric patients. A relatively high failure rate of 10%-25% has been reported, even in experienced hands. It is assumed that this high failure rate of the ILIH nerve block in this age group could be due to lack of special knowledge of the anatomy of these nerves in infants and neonates. There are two main techniques for landmark-based ILIH nerve block with regard to determining the best insertion point. This study compared the sucess rate and outcomes of these two techniques in children undergoing surgery in inguinal region. Patients and Methods: In a double-blind randomized clinical trial, 120 children were candidated for surgery in inguinal region, and ILIH nerve block was recruited in Tabriz Children Teaching Hospital in a 12-month period. They were randomly clustered in two groups and underwent two different methods of ILIH nerve block. In the first group, needle was inserted in a point placed between outer 1/4 and inner 3/4 of a line connecting anterior-superior iliac spine to umbilicus (n = 58), and in the second group, this point was 1 cm medial and 1 cm superior to anterior-superior iliac spine. Block failure was defined as the need for analgesia during operation. Results: There were 50 males (86.2%) and 8 females (13.8%) with a mean age of 5.55 ± 2.32 (3-11) years in the first group and 48 males (87.3%) and 7 females (12.7%) with a mean age of 5.32 ± 2.18 (3-11) years in the second group (P > 0.05). The success rate of ILIH block was 94.8% in the first group and 94.5% in the second group with no significant difference between the two groups (P = 0.64). Changes of vital signs including heart rate, systolic blood pressure, and diastolic blood pressure, as well as the SPO2 were not significantly different between the two groups during the study period. Change of pain severity after recovery was also comparable between the two groups. Time of the first dose of postoperative analgesic was not significantly different between the two groups. Conclusion: Based on our findings, success rate and outcomes of the two techniques of landmark-based ILIH block are similar in children undergoing surgery in inguinal area.